Personagem imortal: a construção da memória de Tiradentes no Museu Paulista e no Museu da Inconfidência - Dolci, Mariana de Carvalho (2014)
This research, entitled "Immortal Personality: the preservation of the memory of Tiradentes in Museu Paulista and in the Museu da Inconfidência" examined how the second Lieutenant Joaquim José da Silva Xavier, known as Tiradentes, and the movement he took part in, Inconfidência Mineira (Minas Conspiracy) were portrayed, explained and immortalized in the Museu Paulista in São Paulo and Museu da Inconfidência in Ouro Preto. Historical museums often treat them, erroneously, as the forerunners of the movement of Brazilian Independence, which would only happen in 1822. This can be explained by the appropriation of the movement by Brazilian Historic and Geographic Institute (IHGB) in the nineteenth century, in order to give coherence to the nationalist movement. However, it is important to respect the specificity of the moment, as the conspirators had no notion that thirty three years later the independence would actually happen. They fought for the emancipation of Minas Gerais. One of the explanations are the reasons why these museums were opened: in São Paulo, the place where the Ipiranga monument was built and later converted into a museum, appears strongly based on tradition and the building alone was considered a historical monument, for having been the site of the proclamation of Brazilian independence. Even though the director of this museum between 1917 and 1945, Affonso d' Escragnolle Taunay, was not a historian, he was the one who planned the entire composition of the internal decoration for the Centennial of Independence in 1922. The Museu da Inconfidência, opened on August 11, 1944, was planned by President Getúlio Vargas. He gave orders to bring back to Brazil the remains of the participants of the Minas Conspiracy who were banished to Africa. The bones that could be exhumed arrived in 1937. At a time when the recovery of the Brazilian memory was becoming a priority for both government and intellectuals, the place to deposit those relics had to be Ouro Preto. Thenceforth, it is possible to understand why Tiradentes and the Minas Conspiracy where chosen to be a part of the exhibitions of these museums